Inter- and intra-population variability in physical dormancy along a precipitation gradient - Ferreras, Ana Elisa (2017)
Physical dormancy enables plants that occur in temporally stochastic and harsh environments to survive; thus, within the distribution area of a species, the percentage of seeds with physical dormancy is expected to increase towardsmore arid and unpredictable areas. Th ere have been no previous studies evaluating both inter and intra-population variability in physical dormancy along a precipitation gradient. Th e aim of this study was to determine the interand intra-population variability in physical dormancy of seeds of Vachellia aroma (Fabaceae) along a precipitation gradient. We collected mature fruits from four localities along a precipitation gradient in central Argentina for animbibition experiment using controlled germination chambers. Changes in physical dormancy were not found along the precipitation gradient; however, a trend toward higher percentage of seed imbibition (lower PY) at the most humid extreme of the gradient was observed. On the contrary, we did observed intra-population variability in three of the four populations, suggesting that most of the populations of V. aroma might have the ability to deal with the environmental variability encountered at local scale. Th is study highlights the importance of studying both interand intra-population variability in physical dormancy.